Different seasons - King, Stephen, 1947- (New York : Viking Press, 1982)
Contents: Hope springs eternal : Rita Hayworth and Shawshank redemption -- Summer of corruption : Apt pupil -- Fall from innocence : The body -- A winter's tale : The breathing method.
Rita Hayworth and Shawshank redemption -- Apt pupil -- The body -- The breathing method.
Also issued online.
Keywords: American fiction -- 20th century